Effective Suppression of Lithium Dendrite Growth Using a Flexible Single‐Ion Conducting Polymer Electrolyte. Issue 31 (3rd July 2018) - Deng, Kuirong; Qin, Jiaxiang; Wang, Shuanjin; Ren, Shan; Han, Dongmei; Xiao, Min; Meng, Yuezhong
Abstract: A novel single‐ion conducting polymer electrolyte (SIPE) membrane with high lithium‐ion transference number, good mechanical strength, and excellent ionic conductivity is designed and synthesized by facile coupling of lithium bis(allylmalonato) borate (LiBAMB), pentaerythritol tetrakis (2‐mercaptoacetate) (PETMP) and 3, 6‐dioxa‐1, 8‐octanedithiol (DODT) in an electrospun poly(vinylidienefluoride) (PVDF) supporting membrane via a one‐step photoinitiated in situ thiol–ene click reaction. The structure‐optimized LiBAMB‐PETMP‐DODT (LPD)@PVDF SIPE shows an outstanding ionic conductivity of 1.32 × 10 −3 S cm −1 at 25 °C, together with a high lithium‐ion transference number of 0.92 and wide electrochemical window up to 6.0 V. The SIPE exhibits high tensile strength of 7.2 MPa and elongation at break of 269%. Due to these superior performances, the SIPE can suppress lithium dendrite growth, which is confirmed by galvanostatic Li plating/stripping cycling test and analysis of morphology of Li metal electrode surface after cycling test. Li|LPD@PVDF|Li symmetric cell maintains an extremely stable and low overpotential without short circuiting over the 1050 h cycle. The Li|LPD@PVDF|LiFePO4 cell shows excellent rate capacity and outstanding cycle performance compared to cells based on a conventional liquid electrolyte (LE) with Celgard separator. The facile approach of the SIPE provides an effective and promising electrolyte for safe, long‐life, and high‐rate lithium metal batteries. Abstract : A novel gel‐state single‐ion conducting polymer electrolyte (SIPE) with high lithium‐ion transference number, good mechanical strength, and excellent ionic conductivity is prepared by a facile and green method. Due to high lithium‐ion transference number and good mechanical strength of LPD@poly(vinylidienefluoride) SIPE, it is able to suppress lithium dendrite growth.